1985
DOI: 10.1097/00000658-198508000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Access for Hemodialysis Patency Rates and Results of Revision

Abstract: Over a 4-year interval, 324 arteriovenous conduits were created in 256 patients with end-stage renal disease as access for chronic hemodialysis. These included 154 Cimino fistulae, 163 polytetrafluoroethylene (PTFE) grafts, and seven miscellaneous grafts. Satisfactory patency rates were demonstrated for as long as 4 years for both Cimino fistulae and PTFE grafts by life-table analysis. Failures of Cimino fistulae usually occurred early in the postoperative period, secondary to attempts to use inadequate veins.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
181
2
20

Year Published

1988
1988
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 487 publications
(212 citation statements)
references
References 11 publications
9
181
2
20
Order By: Relevance
“…The reported complication rates in AVF vary between 21% and 64% (Palder et al 1985), which is similar to that observed in our study. Our results did not show that the complication rate for PTFE grafts was higher than brachiocephalic fistulae, which is consistent with one report (Salahi et al 2006) but opposite to another report (Modarai et al 2005).…”
Section: Discussionsupporting
confidence: 91%
“…The reported complication rates in AVF vary between 21% and 64% (Palder et al 1985), which is similar to that observed in our study. Our results did not show that the complication rate for PTFE grafts was higher than brachiocephalic fistulae, which is consistent with one report (Salahi et al 2006) but opposite to another report (Modarai et al 2005).…”
Section: Discussionsupporting
confidence: 91%
“…This conclusion can vary and depends on many factors, including the definition of access survival, and the age and quality, presentation, and interpretation of the data. For example, the K/DOQI VA guidelines stated that AVF have "excellent patency once established" and "lower complication rates" (14), whereas one study referenced stated "the patency rate of PTFE grafts was significantly (P Ͻ 0.01) better than that for endogenous fistulae" (69). Figure 5 demonstrates superior graft cumulative patency compared with AVF.…”
Section: Impact On the Patient: The Patient Is Firstmentioning
confidence: 99%
“…In patients who have exhausted all options for an upper extremity fistula or graft, placement of a thigh graft is a viable option (3,4). Although thrombosis is the most common complication of grafts, infection is also relatively frequent, affecting 9% to 20% of grafts (5)(6)(7)(8)(9)(10)(11). Graft infections can result in long hospitalizations, serious complications, and prolonged catheter dependence (12).…”
Section: Introductionmentioning
confidence: 99%